2020
DOI: 10.1371/journal.pone.0240942
|View full text |Cite
|
Sign up to set email alerts
|

The utility of urinary biomarker panel in predicting renal pathology and treatment response in Chinese lupus nephritis patients

Abstract: Given the urgent need for non-invasive biomarkers of LN, we aim to identify novel urinary biomarkers that facilitate diagnosis, assessment of disease activity and prediction of treatment response in a retrospective SLE cohort. A total of 154 SLE patients and 55 healthy controls were enrolled, among whom 73 were active LN patients. We measured renal activity by renal SLEDAI. The treatment response of the active LN patients who finished 6-month induction therapy was assessed based on the American College of Rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…These results are not surprising considering that the pathogenic role of all 4 biomarkers is more in keeping with proliferative LN. In addition, we and other groups have shown that all 4 analytes correlate with the activity index in the kidney biopsy ( 16 , 29 , 30 ). A strength of our study is that we validated the proposed biomarkers in three independent cohorts and by 2 different methods of detection, demonstrating the reproducibility of their discriminatory and predictive abilities.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…These results are not surprising considering that the pathogenic role of all 4 biomarkers is more in keeping with proliferative LN. In addition, we and other groups have shown that all 4 analytes correlate with the activity index in the kidney biopsy ( 16 , 29 , 30 ). A strength of our study is that we validated the proposed biomarkers in three independent cohorts and by 2 different methods of detection, demonstrating the reproducibility of their discriminatory and predictive abilities.…”
Section: Discussionsupporting
confidence: 59%
“…All 4 biomarkers, Adiponectin, MCP-1, sVCAM-1 and PF4, have been previously proposed by our group and others as potential biomarkers for ALN ( 15 24 ). In addition, prior studies have shown that all 4 analytes correlate with the activity index in the kidney biopsy ( 16 , 29 , 30 ), suggesting that they play a role in LN pathogenesis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The combination of IgG autoantibodies against heparan sulphate, histone H2B, and vimentin could differentiate NPSLE from non-NPSLE with an AUC of 0.845 ( 86 ). The combination of urinary VCAM-1, CystatinC, and KIM-1 discriminated proliferative LN from membranous LN with an AUC of 0.80 (95%CI: 0.69–0.90) ( 161 ). A combination of five urinary proteins, namely L-PGDS, transferrin, ceruloplasmin, MCP-1, and sVCAM-1 was a good predictor of active LN (AUC= 0.898).A combined model of L-PGDS, transferrin, alpha-1-acid glycoprotein (AGP-1), ceruloplasmin, MCP-1 and sVCAM-1 predicted response to rituximab treatment at 12 months (AUC = 0.818) ( 162 ).…”
Section: Biomarker Panels For Sle: the Destinationmentioning
confidence: 99%
“…The IL-1 family consists of 11 members containing the IL-1 consensus sequence A-X-D, where A is an aliphatic amino acid, X is an arbitrary amino acid, and D is an aspartic acid ( 85 ). It has been shown that IL-18 is of great significance in the early diagnosis of diabetic nephropathy ( 86 ) and lupus nephritis ( 87 ). Although IL-1β has a known critical role in gout, increasing evidence suggests that other IL-1 family members are also involved in the pathogenesis of hyperuricemia and gout flares ( 88 ).…”
Section: Early Biomarkers Of Gout Kidney Injurymentioning
confidence: 99%